THE RELATIONSHIP BETWEEN WORK DEMANDS AND SOCIAL SUPPORT ON WORK STRESS DURING THE PANDEMIC - Sani, Nisrina Tiara; Widajati, Noeroel; Eskartya Harjono, Afrian (Journal of Vocational Health Studies, 2024)
Background: Stress is the effect of competition and high professional demands in the workplace. The Occupational Safety and Health Agency (UPT Keselamatan Kerja) is a technical implementation unit with responsibilities and functions in occupational hygiene, health, and safety. The proliferation of COVID-19 in numerous regions has repercussions for all sectors of society, including agency employees. Those still employed are required to adjust to new conditions. Purpose: Analyse the effect of work demands and social support on work stress among UPT Keselamatan Kerja Surabaya employees during the pandemic. Method: The research was conducted on contract and permanent employees (civil servants), which were divided into three distinct work units: the Safety Training Section Corporate Hygiene and Occupational Safety, the Administration Section, the Testing and Inspection Section. This study employed a quantitative approach. The data were collected using observation. Result: The findings of the study indicated that: 1) UPT Keselamatan Kerja Surabaya employees fell into elevated work demands, 2) UPT Keselamatan Kerja Surabaya employees obtained a high level of social support, 3) Work demands and social support simultaneously affected employees' work stress at UPT Keselamatan Kerja Surabaya. Conclusion: Social support affected work stress among UPT Keselamatan Kerja Surabaya employees with a significance value of 0.004. Work demands and social support concurrently affected the stress experienced by UPT Keselamatan Kerja Surabaya employees.